PERBANDINGAN PENDAPATAN USAHATANI CABAI MERAH (Capsicum annuum L.) SEBELUM DAN SAAT PANDEMI COVID-19 DI DESA GALUNG LOMBOK, KEC. POLIWALI MANDAR - Siska Damayanti; Ikrar Taruna Syah; Nurlela (UIR Press, 2023)
This study aims to compare the income from cayenne pepper farming before and during the COVID-19 pandemic in Galung Lombok Village, Tinambung District, Polewali Mandar Regency. The locus was chosen because it is one of the sweet and chili producing areas, and most of the population works as cayenne pepper farmers. The total respondents in this study were 27 cayenne pepper farmers. This study used a quantitative descriptive method by filling out a questionnaire given to farmers. The data obtained were then analyzed using a paired T-test. The results showed that there were significant differences in the production and income of cayenne pepper farmers before and during the COVID-19 pandemic, While the total production increased significantly, the total income of farmers decreased significantly during the pandemic. The results of this study can be used as a consideration for the government in determining policy, especially regarding the price of cayenne pepper during a pandemic, and not only focusing on policies at the upstream level.